Pengaruh Penerapan Model Pembelajaran Project Based Learning dengan Pendekatan Design Thinking terhadap Kemampuan Berfikir Kreatif - Purbianti, Rita; Jailani, Jailani; Turista, Dora Dayu Rahma; Makkadafi, Suparno Putera; Serena, Nelda Anasthasia (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research is motivated by the lack of variety in learning models implemented at SMPN 45 Samarinda, which causes students to tend to be passive and lack creative thinking skills. This study aims to analyze the effect of the Project-Based Learning (PjBL) model with a Design Thinking approach on the creative thinking skills of seventh-grade students. The method used was a quasi-experimental design with a nonequivalent control group design. The sample consisted of two classes: VIIA as the experimental class and VIIB as the control class, each with 25 students. The research instrument was a pre-test and post-test essay test based on creative thinking indicators. Data analysis used an Independent Sample t-Test with a significance level of 5%. The results showed that the calculated t value (20.545) > t table (1.677), so H0 was rejected and Ha was accepted. Thus, the implementation of the Design Thinking-based PjBL model had a significant effect on improving students' creative thinking skills.